A hit deconstruction approach for the discovery of fetal hemoglobin inducers. Issue 23 (15th December 2018) - Benowitz, Andrew B.; Eberl, H. Christian; Erickson-Miller, Connie L.; Gilmartin, Aidan G.; Gore, Elizabeth R.; Montoute, Monica N.; Wu, Zining
Graphical abstract: Highlights: Benzoxaborole compounds can be optimized by deconstruction and reconstruction. The compounds have been optimized for cellular HbF induction, solubility, and PK. The optimized compounds inhibit key RNA processing proteins. Abstract: Beta-hemoglobinopathies such as sickle cell disease represent a major global unmet medical need. De-repression of fetal hemoglobin in erythrocytes is a clinically validated approach for the management of sickle cell disease, but the only FDA-approved medicine for this purpose has limitations to its use. We conducted a phenotypic screen in human erythroid progenitor cells to identify molecules with the ability to de-repress fetal hemoglobin, which resulted in the identification of the benzoxaborole-containing hit compound1 . This compound was found to have modest cellular potency and lead-like pharmacokinetics, but no identifiable SAR to enable optimization. Systematic deconstruction of a closely related analog of1 revealed the fragment-like carboxylic acid12, which was then optimized to provide tetrazole31, which had approximately 100-fold improved cellular potency compared to1, high levels of oral exposure in rats, and excellent solubility.